1997
DOI: 10.1074/jbc.272.36.22456
|View full text |Cite
|
Sign up to set email alerts
|

Improved Activity and Modulated Action Pattern Obtained by Random Mutagenesis at the Fourth β-α Loop Involved in Substrate Binding to the Catalytic (β/α)8-Barrel Domain of Barley α-Amylase 1

Abstract: ␣-Amylase (␣-1,4-D-glucan glucanohydrolase, EC 3.2.1.1) hydrolyzes internal ␣-1,4-glucosidic bonds in starch and related oligo-and polysaccharides. High resolution x-ray structures are known for Taka-amylase A (TAA) 1 from Aspergillus oryzae(1), acid ␣-amylase from Aspergillus niger (2), isozyme I of porcine pancreatic ␣-amylase (PPA; Ref.3), the AMY2-2 isoform from barley malt (4), and an inactive, protease-cleaved form of ␣-amylase from Bacillus licheniformis (5). These enzymes are organized in three domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(88 citation statements)
references
References 64 publications
(76 reference statements)
1
87
0
Order By: Relevance
“…For the triple mutant K193A/R194A/ K195A, the K m value increased markedly and the k cat value decreased moderately. The negatively charged triple mutant K193E/R194E/K195E showed similar but more magnified effects on both parameters compared with the alanine triple mutant K193A/R194A/K195A, indicating ionic interactions of the positive cluster with DNA phosphate groups in an analogous manner to Arg 40 and Arg 42 on small loop 1. The values of K199A differed little from those of WT.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…For the triple mutant K193A/R194A/ K195A, the K m value increased markedly and the k cat value decreased moderately. The negatively charged triple mutant K193E/R194E/K195E showed similar but more magnified effects on both parameters compared with the alanine triple mutant K193A/R194A/K195A, indicating ionic interactions of the positive cluster with DNA phosphate groups in an analogous manner to Arg 40 and Arg 42 on small loop 1. The values of K199A differed little from those of WT.…”
Section: Resultsmentioning
confidence: 82%
“…The K a value of R40G/R42G and R118A/ K119A dropped 6-and 4-fold, respectively, and the values for each single mutant decreased moderately compared with that of WT, whereas the K a value of the other mutants showed little difference to that of WT. The results indicated that both these sites, Arg 40 archaea (14, 18) for which differences in substrate binding were proposed. According to the two-modeled structures of the protein-substrate complex, the 5Ј end of the single-stranded flap strand threads through the hole formed by the L1 loop (corresponding to the large loop in our work).…”
Section: Kinetic Parameter Of Mutants On Four Small Loops and One Larmentioning
confidence: 82%
See 3 more Smart Citations